Sistem Penjualan dan Simpan Pinjam pada koperasi Harum Sari PT. Air Mancur - Hardi Santoso Sri Hariyati Fitriasih (Jurnal Ilmiah SINUS, 2011)
The Application System Cooperative Harum Sari PT. Air Mancur. Fountain is based on the design of a system consisting of Diagram Context (Context Diagram), Hierarchy Input Process Output (HIPO), Data Flow Diagram (DAD), Entity Relationship Diagram (ERD) which consists of 13 tables, namely: A table, table goods, table suppliers, purchasing tables, table dbeli, sales table, table djual, Table returns, dretur table, table to save, borrow table, table pieces. Reports from the data processing application inventory includes: data reports members, reports the data item, supplier data reports, reports global security be good purchases, daily, monthly, reports sales of goods transasksi good credit and cash globally, daily, monthly, reports transasksi save, borrow transasksi reports, transaction reports cooperative pieces, SHU division reports, report taking deposits Keywords : Savings and Loans